In a blue room - Averbeck, Jim.; Tusa, Tricia (Orlando [Fla.] : Harcourt, 2008)
Alice wants everything in her bedroom to be blue before she falls asleep.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Keywords: Bedtime -- Juvenile fiction; Blue -- Juvenile fiction; Mother and child -- Juvenile fiction; Children's stories -- Pictorial works